Analisis Peran Developer PT. X Sidoarjo dalam Evaluasi Kesiapan Konsumen pada Proses Pengajuan KPR - Fiola Haliza Putri Rosniar; G. Oka Warmana (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
The Home Ownership Loan (KPR) application process often faces failure or delays not only due to financial inability but also due to consumers' administrative unreadiness. This study aims to analyze the strategic role of Developer PT. X Sidoarjo in evaluating consumer readiness at the pre-application stage to mitigate the risk of credit rejection. This research employs a descriptive qualitative method, with data collected through direct observation of the pre-application workflow and a literature review on credit administration procedures. The results indicate that the developer acts as an initial filter through the functions of requirement education, verification of document completeness and credit history (SLIK), and financial capability mapping via installment simulations. Consumer readiness indicators are assessed based on file completeness, data consistency, and responsiveness during verification. Risk mitigation strategies are implemented through adjustments to the Down Payment (DP) amount and selecting partner banks that match the consumer's risk profile. It is concluded that early evaluation performed by the developer at the pre-application stage is effective in minimizing repeated file revisions and streamlining the approval process by the bank